THE EVOLUTION OF ENGLISH AS A GLOBAL LANGUAGE (INGLIZ TILINING GLOBAL TILGA AYLANISHI) - Fayzullayeva Ruxsora Jamoldinovna; Hamidov Nodirbek (TADQIQOTLAR, 2025)
Abstract: This article explores the transformation of the English language from a regional dialect into a global lingua franca. By examining historical, political, economic, and technological factors, the study outlines the reasons for English’s widespread use today. It also addresses challenges associated with linguistic dominance, such as cultural erosion and language endangerment. The research reflects on how English shapes identity, communication, and global relations in the modern era.